Pengaruh Service Quality dan Costumer Experience Terhadap Niat Penggunaan Ulang Jasa Transportasi Kereta Api Indonesia (KAI) Stasiun Tanjung Balai - Jafar Syahbuddin Ritonga; Yuni Syahputri; Rini Damayanti (ARBITRASE: Journal of Economics and Accounting, 2022)
The focused of this paper was to examine and analyze the influence of service quality and customer experience on reuse intention of Indonesian railway service in Tanjungbalai stasion. The literature review of this paper obtained from the similar previous journal researchs to found the hypothesis of this research. Data collected by questionnaire distribution to 100 respondents were selected by Nonprobability sampling with total 27 statements were measured by Likert scale. Data analyzed by quantitative method such as validity and reliability test, classic assumption tes, multiple regression linear, and hypothesis test were processed by software SPSS 25. The data processing result indicated that the instruments of questionnaire were valid and reliable, the data were distributed normally, there were no heteroscesdasticity and multicollinearity and whole of the service quality variabel and customer experience variabel hypothesis has influenced positively and significantly toward the reuse intension as dependent variabel based on result of partial and simultaneous hypothesis test.